2017
DOI: 10.1136/neurintsurg-2017-013466
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion for anterior choroidal artery (AChA) aneurysms: a multi-institutional experience

Abstract: The PED can be used successfully in AChA aneurysms with a good safety and efficacy profile. All AChAs remained patent. Collateral flow networks, especially for the ACA, affect long-term branch vessel patency. Treatment with PED for AChA aneurysms appears to be a reasonable option to consider and should be evaluated in a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…However, certain aneurysms in these locations are considered for FD specifically because they are not amenable to surgical clipping or endovascular coiling because of their complex fusiform morphology and/or giant size. Our previous experience in covering large or essential vessels with FDs did not show clinically significant infarcts, 26 which is similar to other reports. 18,21,23,27,31 Here, we present a multicenter experience for treating distal ICA aneurysms and proximal MCA and ACA aneurysms with the Pipeline embolization device (PED; Medtronic) covering medial and lateral lenticulostriate vessels.…”
supporting
confidence: 90%
“…However, certain aneurysms in these locations are considered for FD specifically because they are not amenable to surgical clipping or endovascular coiling because of their complex fusiform morphology and/or giant size. Our previous experience in covering large or essential vessels with FDs did not show clinically significant infarcts, 26 which is similar to other reports. 18,21,23,27,31 Here, we present a multicenter experience for treating distal ICA aneurysms and proximal MCA and ACA aneurysms with the Pipeline embolization device (PED; Medtronic) covering medial and lateral lenticulostriate vessels.…”
supporting
confidence: 90%
“…Because the AchA supplies the blood flow to the eloquent areas, 12 which have a high flow demand, such as the posterior limb of the internal capsule, the optic radiation, the acoustic radiation, the internal (medial) globus pallidus, the tail of the caudate nucleus, the uncinate gyrus, the head of the hippocampus, the amygdala, the piriform cortex and the lateral geniculate body, occlusion of the AchA is considered to be extremely rare. 21 Chen et al 22 reported a case in which, although there was an occlusion at the distal end of the FD after FD deployment for an unruptured aneurysm in the internal carotid artery, the flow to the middle cerebral artery was preserved using a pipeline strut. The authors described the event as being caused by the flow demand in the region supplied by the middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Regarding the anterior choroidal artery, an extremely low occlusion rate was reported. [11][12][13][14][15][16] NMC Case Report Journal Vol. 8,2021 In this study, we described a rare case of delayed anterior choroidal artery occlusion which led to critical neurological deficit following the deployment of a flow diverter stent for a large internal carotid artery aneurysm.…”
Section: Introductionmentioning
confidence: 99%